2018
DOI: 10.1002/1878-0261.12162
|View full text |Cite
|
Sign up to set email alerts
|

TGF‐β transactivates EGFR and facilitates breast cancer migration and invasion through canonical Smad3 and ERK/Sp1 signaling pathways

Abstract: Transforming growth factor‐beta (TGF‐β) functions as a potent proliferation inhibitor and apoptosis inducer in the early stages of breast cancer, yet promotes cancer aggressiveness in the advanced stages. The dual effect of TGF‐β on cancer development is known as TGF‐β paradox, and the remarkable functional conversion of TGF‐β is a pivotal and controversial phenomenon that has been widely investigated for decades. This phenomenon may be attributed to the cross talk between TGF‐β signaling and other pathways, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(98 citation statements)
references
References 44 publications
4
94
0
Order By: Relevance
“…Western blot assay was performed as described previously [44]. Briefly, the cells were lysed with 1× SDS lysis buffer; the cell lysates after protein quantification were used for SDS-PAGE separation and subsequently transferred to a PVDF membrane.…”
Section: Western Blot and Co-immunoprecipitation Assaymentioning
confidence: 99%
“…Western blot assay was performed as described previously [44]. Briefly, the cells were lysed with 1× SDS lysis buffer; the cell lysates after protein quantification were used for SDS-PAGE separation and subsequently transferred to a PVDF membrane.…”
Section: Western Blot and Co-immunoprecipitation Assaymentioning
confidence: 99%
“…Abnormal expression of SP1 is often associated with the occurrence and progression of tumors. Many studies have shown that the expression of SP1 in gastric cancer [12], pancreatic cancer [13] and breast cancer [14] is significantly higher than that in corresponding normal tissues. Inhibition of SP1 expression could significantly impede cell proliferation and cell cycle progression in TSCC cell lines [15].…”
Section: Introductionmentioning
confidence: 99%
“…SMAD3 is a member of the SMAD3 family which functions as a direct mediator of TGFnucleus [27]. Alteration of the TGF-, and invasion of different types of cancers, like breast cancer and glioma [28,29]. Zhao et al found that SMAD3 could be regulated by TCF and JUN through interactions with histone deacet ylases and acetyltransferases [30].…”
Section: Discussionmentioning
confidence: 99%